2021
DOI: 10.1111/jdv.17710
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate exhibits anti‐inflammatory effects in a human interface dermatitis model—implications for therapy

Abstract: Background Epigallocatechin-3-gallate (EGCG) has been proven effective in treating viral warts. Since anticarcinogenic as well as anti-inflammatory properties are ascribed to the substance, its use has been evaluated in the context of different dermatoses. The effect of EGCG on interface dermatitis (ID), however, has not yet been explored. Objectives In this study, we investigated the effect of EGCG on an epidermal human in vitro model of ID.Methods Via immunohistochemistry, lesional skin of lichen planus pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Polyphenols naturally derived phytochemical compounds have been reported in the potential treatment of AD. , These compounds have multiple hydroxylated aromatic rings that exert anti-inflammatory effects and scavenge ROS similar to superoxide dismutase (SOD). Among the variety of polyphenols, epigallocatechin-3-gallate (EGCG) has been recently effective in AD treatment. , In the AD mouse model, EGCG treatment significantly alleviates the disruption of the skin barrier by inhibiting the macrophage migration inhibitory factor (MIF) and various cytokines (e.g., IL-2, IL-12 p40, TNF-α, IFN-γ, etc.) related to AD pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols naturally derived phytochemical compounds have been reported in the potential treatment of AD. , These compounds have multiple hydroxylated aromatic rings that exert anti-inflammatory effects and scavenge ROS similar to superoxide dismutase (SOD). Among the variety of polyphenols, epigallocatechin-3-gallate (EGCG) has been recently effective in AD treatment. , In the AD mouse model, EGCG treatment significantly alleviates the disruption of the skin barrier by inhibiting the macrophage migration inhibitory factor (MIF) and various cytokines (e.g., IL-2, IL-12 p40, TNF-α, IFN-γ, etc.) related to AD pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Among the variety of polyphenols, epigallocatechin-3gallate (EGCG) has been recently effective in AD treatment. 9,10 In the AD mouse model, EGCG treatment significantly alleviates the disruption of the skin barrier by inhibiting the macrophage migration inhibitory factor (MIF) and various cytokines (e.g., IL-2, IL-12 p40, TNF-α, IFN-γ, etc.) related to AD pathogenesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), a natural polyphenol found in green tea, has many biological activities, including anti-inflammatory, antioxidant, cardioprotective, neuroprotective, and anticancer activities (Nan et al, 2019;Yi et al, 2020;Nan et al, 2021). Studies have revealed EGCG as a potential therapeutic agent for various skin inflammation conditions, including psoriasiform dermatitis (Chamcheu et al, 2018), interface dermatitis (ID) (Braegelmann et al, 2022), and atopic dermatitis (AD) (Noh et al, 2008). Although a clinical trial of four healthy volunteers demonstrated the potential anti-angiogenic effect of EGCG cream (Domingo et al, 2010), whether EGCG has a therapeutic effect on rosacea remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, epigallocatechin-3-gallate (EGCG) is the major catechin found in green tea. It is among natural products that have recently attracted the attention of researchers due to its antioxidant (Dewaantari et al, 2021), anti-inflammatory (Braegelmann et al, 2021), anti-apoptotic (Zong et al, 2021), and anticancer (Zhu et al, 2021) properties. Moreover, in several models, ECCG has shown to be renoprotective (Kanlaya & Thongboonkerd 2019), neuroprotective , and anti-diabetic (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%